KLASIFIKASI INDEKS PEMBANGUNAN MANUSIA DI INDONESIA TAHUN 2022 DENGAN SUPPORT VECTOR MACHINE - Pamungkas, Canggih Ajika; Widiyanto, Wahyu Wijaya (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2022)
The success of national development apart from being seen from the high rate of economic growth, the most important thing is the success in the aspect of human development. The Human Development Index is a measure used to monitor and evaluate human development. The purpose of this study is to measure the classification accuracy of the Human Development Index in Indonesia in 2022 with the Support Vector Machine (SVM) and a performance measurement tool for classification problems, namely the Confusion Matrix. Based on the research results, it can be obtained that the percentage accuracy of the classification of the Human Development Index in Indonesia in 2022 with the Support Vector Machine (SVM) is not directly proportional to the increase in the amount of training data, this conclusion implies that it is necessary to consider scientifically in determining the ratio of testing data and training data.